A balada de Mary Hynes en clave galego-irlandesa: Luz Pozo Garza e W. B. Yeats - Piñeiro Domínguez, María Jesús (Madrygal. Revista de Estudios Gallegos, 2009)
We have chosen the story of Mary Hynes, an Irish girl of incomparable beauty that Raftery made popular, to bring close together two versions of this ballad: William Butler Yeats’s and Luz Pozo Garza’s. We prove thus how both writers promote the Atlantic European literature and build literary bridges between Galicia and Ireland that go beyond time and space.